Webinar report: Potato Seed Production Technology in Southeast Asia – with special focus on Vietnam and Philippines - International Potato Center (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Consumption of potatoes and potato products is growing rapidly in Southeast Asia. There are significant opportunities for improved potato production and utilization of technologies in this part of the world to address poverty, food security, and environmental degradation. Potato production is also a highly profitable activity. The market for fresh consumption of potatoes is expanding in most of Asia in response to income growth and urbanization. However, potatoes are a high input, high risk crop - where there is always the chance of completely losing the crop to climatic stressors like typhoons, heavy rainfall, or drought. In Indonesia, Philippines, VietNam and Thailand small farms predominate, and production is very labor intensive, and even small farms may make extensive use of hired labor in potato cultivation, employing landless workers. Potato production in these countries is commercially oriented with more than 80 percent of the harvested crop being sold. The most significant risk a farmer must face is that associated with the high price of seed and its availability in a timely manner.